Damage effects and mechanisms in granite treated with acidic chemical solutions. (October 2016) - Miao, Shengjun; Cai, Meifeng; Guo, Qifeng; Wang, Peitao; Liang, Mingchun
Abstract: Uniaxial and triaxial compression tests as well as splitting tests were conducted on granite specimens after acidic solution erosion at a variety of different pH values and flow rates. The responses of strength loss, deformation behavior and mechanical parameters of the granite were compared and analyzed. The effects of acidic chemical corrosion on microscopic structures, defect morphology and mineral elements of the granite were observed and analyzed under scanning electron microscopy (SEM) and electron spectroscopy. The aging that resulted from the interactions between the granite and chemical solutions were analyzed based on the mass and elastic wave velocity data of the specimens and pH value of the solutions at different soaking times, along with ion chromatography detection results of the solutions' chemical constituents and concentrations after soaking. Based on the results of X-ray diffraction for the mineral composition and X-ray fluorescence to determine the chemical elements and compounds in granite, the chemical reactions between granite and acidic solutions as well as the damage mechanism underlying the interaction were discussed in the theoretical context of chemical kinetics. Highlights: The responses of strength loss, deformation behavior and mechanical parameters of the granite after treatment with acidic solutions were compared and analyzed. The effects of acidic chemical corrosion on microscopic structures, defect morphology and mineral elements of the granite were observed and analyzed. The aging of granite damage which resulted from the interactions between the granite and acidic solutions were analyzed. The chemical reactions between granite and acidic solutions as well as the mechanism underlying the chemical damage of granite subjected to acidic solution were discussed and revealed.